Thrombolysis in the developing world: is there a role for streptokinase?. Issue 7 (21st January 2013) - Butcher, Ken; Shuaib, Ashfaq; Saver, Jeffrey; Donnan, Geoffrey; Davis, Stephen M.; Norrving, Bo; Wong, K. S. Lawrence; Abd‐Allah, Foad; Bhatia, Rohit; Khan, Adnan
Abstract : Intravenous thrombolysis with tissue plasminogen activator is the only proven acute therapy for ischemic stroke. This therapy has not been translated into clinical practice in the developing world primarily due to economic constraints. Streptokinase, a lower cost alternative thrombolytic agent, is widely available in developing countries where it is utilized to treat patients with acute coronary syndromes. Although this drug has previously been found to be ineffective in ischemic stroke, the lack of benefit may have been related to a number of factors related to trial design rather than the drug itself. Specific features of prior trial designs that may have adversely affected outcomes include a prolonged treatment window, inclusion of patients with established infarction on computed tomography scan, failure to treat excessive arterial pressures, a fixed dose of streptokinase, and concomitant use of antithrombotic medications. Given the lack of therapeutic alternatives in developing countries, a new trial of streptokinase in acute stroke, utilizing stricter inclusion criteria similar to those in more recent thrombolytic studies, appears warranted.